Negative effect of turbidity on prey capture for both visual and non‐visual aquatic predators. Issue 11 (26th September 2020) - Ortega, Jean C. G.; Figueiredo, Bruno R. S.; da Graça, Weferson J.; Agostinho, Angelo A.; Bini, Luis M.
Abstract: Turbidity plays an important role in aquatic predator–prey interactions. Increases in turbidity are expected to reduce prey capture rates, especially for visually oriented predators. However, there is also evidence indicating that turbidity may have little or no effect on predation rates. Here, we conducted a systematic review and meta‐analysis of the relationship between turbidity and capture rate. We explored possible sources of heterogeneity in the effect sizes (capture strategy, predator's body size, relative eye size and turbidity range in the experiments) while controlling for the dependence among effects sizes and phylogenetic relationships among predator species. We found a consistent negative effect of turbidity on prey capture and that turbidity range (manipulated in the experiments) was the main factor accounting for between‐study variation in effect sizes. Also, capture rates of both visually and non‐visually oriented predators decreased with an increase in turbidity. In addition, for visually oriented fish predators, the relative eye size did not influence the effect sizes. Despite the paucity of studies for some groups of aquatic predators (mainly in tropical regions), we provide corroborative evidence that turbidity is a critical environmental factor controlling predator–prey interactions. This result is especially relevant considering that changes in turbidity is a human‐induced pervasive environmental alteration resulted from, among other mechanisms, runoff after deforestation, eutrophication or oligotrophication in reservoir cascades, which imply changes in predator–prey interactions. Abstract : This meta‐analysis shows that turbidity reduces prey capture by aquatic predators with different predation strategies. Only the range in turbidity explains differences among experiments. These results highlight that turbidity drives predator‐prey dynamics in aquatic environments and draws attention to current and projected changes in water transparency caused by anthropogenic activities.